A new tibial torsiometer applicable to clinical practice - Šestan, Branko (Array, 2009)
Abstract: This study evaluated a new tibial torsiometer that is universally applicable to all limb sizes and requires no special training, jigs, or radiographic equipment. To compare the reliability of measurements obtained with the torsiometer, 160 tibias were evaluated with both the torsiometer and computed tomography. Results for both methods were identical in 51 tibias, within 1° in 66 tibias, and within 2° in 43 tibias. The difference between the two methods was not significantly different. No significant differences were found among examiners. This device should prove to be useful for the quantification of tibial torsion